Tourism - Robinson, Peter, 1979-; Lück, Michael, 1966-; Smith, Stephen L. J., 1946- (CABI, 2020)
"Authored by established experts, fully revised Tourism, 2nd edition covers aspects of tourism from a modern perspective, providing students with a range of theoretical and research-based explanations, supported by examples, case studies and unique insights from industry representatives"- Resumé vydavatel
Keywords: cestovní ruch; management cestovního ruchu; management destinací; tourism; tourism management; destination management; učebnice; textbooks